THE IMPACT OF THE DIGITAL ENVIRONMENT IN THE CONTEXT OF HUMAN RESOURCE MANAGEMENT - Carmen Maria MIHALCEA (Annals of the University of Craiova: Economic Sciences Series, 2023)
The human resource is the fundamental element in the dynamics of any organization, regardless of the field of activity or the constraints of the economic environment. Under these conditions, the importance enjoyed by the human resource management component at the organizational level is obvious. Any analysis of the components of organizational management relies, overwhelmingly, on the multifaceted and complex approach of the dynamics of individuals in the organization, of the tools and mechanisms available to the manager for the formation, consolidation and development of a performing team capable of meeting the requirements imposed by the specific competitive environment the markets on which the entity operates but, at the same time, and perhaps most importantly, from the perspective of the subject of the present paper, the dynamics of the labor market.